Pemanfaatan Teknologi Digital sebagai Media Pembelajaran PAI di Sekolah Dasar pada Era Society 5.0: Sebuah Kajian Sistematis - Muhammadiyah, Muhammadiyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This study is a Systematic Literature Review (SLR) study that aims to analyze trends, types of media, impacts, and challenges of the use of digital media in the learning of PAI in Elementary School in the 2021–2025 period. A total of 11 scientific articles were analyzed based on relevance, methodology, and research results. The findings show that the use of digital technologies such as Canva, Wordwall, learning videos, and interactive e-books has increased significantly in supporting student engagement and learning outcomes. Digital media has proven to be effective in increasing understanding of concepts and learning motivation, although its implementation is still constrained by teacher readiness and infrastructure limitations. This study emphasizes the importance of teacher training and sustainable policy support to optimize the digital transformation of PAI learning at the elementary level.